Superiority of Laparoscopic Gastrojejunostomy Combined With Multimodality Therapy for Gastric Outlet Obstruction Caused by Advanced Gastric Cancer - Wang, Chuandong; Zhang, Xiaojuan; Lin, Shengtao; Yang, Changshun; Zhou, BiaoHuan; Mi, Yulong; Ye, Rong; Chen, Yifan; Chen, Weijie; Lin, Xiaojun; Tan, Song; Zhou, Yuhang; et al. (Frontiers in Oncology, 2022)
Background: Data are limited concerning the survival outcomes of patients with gastric outlet obstruction (GOO) caused by advanced gastric cancers according to laparoscopic gastrojejunostomy (LGJ) combined with multimodality therapy (MMT). Therefore, the purpose of this study was to examine the feasibility and efficacy of these therapies. Methods: This single-centered, retrospective analysis included data of 184 patients with GOO due to advanced gastric cancer (AGC). Treatment models were: laparoscopic gastrojejunostomy combined with multimodality therapy (LGJ+MMT), endoscopic metal stent placement combined with multimodality therapy (EMSP+MMT), and multimodality therapy (MMT). Results: Improved oral intake, better nutritional indices, and better response to chemotherapy were observed in the LGJ+MMT group. Subsequent gastrectomy was performed in 43 (61.4%) patients in the LGJ+MMT group, 23 (37.7%) in the EMSP+MMT group, and 11 (20.8%) in the MMT group (P<0.001). LGJ+MMT was associated with better long-term prognosis. As confirmed by propensity scores and multivariate analyses, the 3-year survival rates in the three treatment models were 31.4% with LGJ+MMT, 0% with EMSP+MMT, and 0% with MMT in conversion therapy, and 50.0% with LGJ+MMT, 33.3% with EMSP+MMT, and 23.5% with MMT in NAC. A forest plot revealed that LGJ+MMT was related to a decreased risk of death. Conclusions: LGJ combined with MMT was associated with better nutritional status, higher rates of subsequent gastrectomy, and good prognosis. LGJ combined with MMT may improve the long-term survival of patients with GOO caused by AGC.